2015
DOI: 10.1111/jth.12967
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative modifications of von Willebrand factor in patients with essential thrombocythemia and controlled platelet count

Abstract: quantitative modifications of von Willebrand factor in patients with essential thrombocythemia and controlled platelet count. J Thromb Haemost 2015; 13: 1226-37.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 67 publications
0
63
2
1
Order By: Relevance
“…Importantly, individuals with concomitant AVWS were also characterized by higher erythrocyte counts than the remaining subjects, which suggests the potential involvement of increased shear stress in the etiopathogenesis of this bleeding disorder. Also some ET-specific etiopathogenetic mechanisms of AVWS, such as in vivo platelet activation, 25 should be considered.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, individuals with concomitant AVWS were also characterized by higher erythrocyte counts than the remaining subjects, which suggests the potential involvement of increased shear stress in the etiopathogenesis of this bleeding disorder. Also some ET-specific etiopathogenetic mechanisms of AVWS, such as in vivo platelet activation, 25 should be considered.…”
Section: Resultsmentioning
confidence: 99%
“…The main abnormalities consisted of loss of larger VWF multimers and high proteolysis of VWF, all associated with thrombocytosis, mostly resulting in bleeding . In a previous study on ET, we observed a deficiency of VWF activity and selectively of large VWF multimers over a wide range of platelet counts, rather than in patients with severe thrombocytosis only . This acquired VWF deficiency was likely a continuous phenomenon, driven by high ongoing in vivo platelet activation, which is the hallmark of ET, with consequent platelet‐dependent VWF consumption …”
Section: Introductionmentioning
confidence: 79%
“…VWF:Ag and VWF:Act levels in 41 patients with PV were also compared to the levels measured in 41 patients with ET selected from a previously‐published cohort to be sex, age, and blood group matched with patients with PV (Table ) . While VWF:Ag levels were similar in patients with PV and ET (Figure A), the VWF:Act values were significantly higher in patients with PV as compared to patients with ET (Figure A), and VWF:Act/VWF:Ag ratios were also higher in patients with PV as compared to patients with ET (Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our cohort, a high percentage of AVWS was found. In contrast, adult studies looking at AVWS in ET reported a much lower prevalence (about 20% of patients) . Nevertheless, Mital et al noted that their younger adult patients developed AVWS more commonly.…”
Section: Discussionmentioning
confidence: 94%